Investigating the renoprotective effects of Polygonatum sibiricum polysaccharides (PSP) on D-galactose-induced aging mice: insights from gut microbiota and metabolomics analyses - Huang, Rui; Che, Runli; Sun, Taoli; Xie, Wen; Zhang, Shuihan (Frontiers in Microbiology, 2025)
IntroductionPolygonatum sibiricum polysaccharides (PSP) have been suggested to possess various health benefits, including anti-aging and renoprotective effects. However, the mechanisms underlying PSP’s protective effects on kidney function, particularly in the context of aging, remain unclear. This study explores how PSP protects against D-galactose (D-gal)-induced kidney damage in aging mice, focusing on gut microbiota and metabolomics.MethodsMice were assigned to five groups: control, model (D-gal), vitamin C, low-dose PSP, and high-dose PSP, and treated for 8 weeks. Kidney pathology was assessed via H&E and Masson’s trichrome staining. 16S rRNA sequencing analyzed gut microbiota, and non-targeted metabolomics identified metabolic changes. Correlations between gut bacteria and metabolites were examined.ResultsPSP alleviated renal damage, reducing tubular atrophy, epithelial swelling, and collagen deposition. It increased beneficial gut bacteria (e.g., Lactobacillus, Bifidobacterium) and altered 23 metabolites linked to pathways such as amino acid and sphingolipid metabolism. Gut microbiota and metabolites were strongly correlated, indicating PSP’s role in regulating the gut-kidney axis.ConclusionPSP protects against age-related kidney damage by modulating gut microbiota and metabolic pathways, highlighting its therapeutic potential for kidney aging through the gut-kidney axis.